Personality traits and self-presentation tactics - Belić, Milena; Vrcić Amar, Anida (Psihološka istraživanja, 2022)
Self-presentation is a omnipresent form of behavior that involves building a self-image in front of other people. It is a form of behavior that aims to structure the impression of a person. Self-presentation explains numerous social relations and situations, but it also depends on numerous factors, primarily personality factors, and numerous situational factors. The main goal of this research is to examine the relationship between broad personality dimensions, operationalized by the Big Five +2 personality model (Neuroticism, Extraversion, Aggression, Conscientiousness, Openness, Positive Valence and Negative Valence) and self-presentation. The possibility of predicting self-presentation in total as well as some of its individual tactics, based on broad personality dimensions was also examined. The survey used the Big 5 + 2 Personality Questionnaire and the Self-Presentation Tactics Scale. The sample included 526 respondents. Of all the examined personality dimensions, Neuroticism and Negative Self-Image have the strongest correlations with overall self-presentation. The Conscientiousness dimension records the highest number of negative correlations, while the Openness dimension records the lowest number of statistically significant correlations with overall self-presentation and individual self-presentation tactics. As for the prediction of self-presentation, all dimensions of personality, except Openness, are important predictors, but their constellation is different in relation to the content of self-presentation tactics. These findings make it possible to predict the direction of the presentation of self image. Namely, knowing the personality traits, we can assume which self-presentation tactics will be used, especially in a situation when people are motivated to do so
Keywords: self-presentation; self-presentation tactics; personality traits